2014
DOI: 10.1001/jamasurg.2013.3970
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Prophylactic Inferior Vena Cava Filters in Trauma Patients

Abstract: The strength of evidence is low but supports the association of IVC filter placement with a lower incidence of PE and fatal PE in trauma patients. Which patients experience benefit enough to outweigh the harms associated with IVC filter placement remains unclear. Additional well-designed observational or prospective cohort studies may be informative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 43 publications
(40 reference statements)
4
97
0
Order By: Relevance
“…Which patients will derive enough benefit from filter deployment to outweigh the long-term complications remains unclear. As a matter of fact, the initiation of anticoagulation in patients considered to have bleeding diathesis is actually safer than originally thought, as shown by different retrospective and prospective studies (16). In almost two-thirds of our patients, anticoagulation was prescribed before discharge, indicating that contraindication for anticoagulation (if present when filter was placed) had subsided.…”
Section: Discussionmentioning
confidence: 62%
“…Which patients will derive enough benefit from filter deployment to outweigh the long-term complications remains unclear. As a matter of fact, the initiation of anticoagulation in patients considered to have bleeding diathesis is actually safer than originally thought, as shown by different retrospective and prospective studies (16). In almost two-thirds of our patients, anticoagulation was prescribed before discharge, indicating that contraindication for anticoagulation (if present when filter was placed) had subsided.…”
Section: Discussionmentioning
confidence: 62%
“…As such, there is an ongoing debate about the appropriateness of prophylactic IVCF placement in these high-risk patients. A recent review and meta-analysis found a decreased incidence of PE with prophylactic IVCF placement, although this was with low strength of evidence [35]. This meta-analysis included six studies to examine PE rates and only four studies to examine fatal PE.…”
Section: Research In Indicationsmentioning
confidence: 99%
“…LMWH has been demonstrated to be safe and effective in trauma patients and is the approach recommended by the East Surgical Group and the current ACCP guidelines [ 34 , 35 ]. In trauma patients at high risk of bleeding the placement of a removal IVC fi lter may be a suitable strategy [ 36 ].…”
Section: The Veins Of the Lower Limbmentioning
confidence: 99%